The effects of training based on BASNEF model and acupressure at GB21 point on the infants' physical growth indicators - marzieh akbarzadeh; nasrin bahmani; marzieh moattari; Saeede PourAhmad (Mashhad University of Medical Sciences, 2014)
objective: Educational models are used to study the behavior and plan for changing and determining the factors that affect the individuals' decision making for conducting a behavior. This study aimed to compare the effects of the educational program based on BASNEF model and acupressure at GB21 point on the infants' physical growth indicators.Methods: This clinical trial was conducted on 150 (50 per group) pregnant women in 2011-2012. The interventions included educational program based on the BASNEF model and application of acupressure at GB21 point. The infants' physical indicators were compared to the control group one and three months after birth. The study data were analyzed using repeated measurement test, paired sample T-Test, one-way ANOVA, and Tukey's test.finding: The results showed a significant difference between the intervention and the control group regarding the infants' weight and height one and three months after birth (p0.05). Also, no significant difference was observed among the three groups concerning the infants' head and arm circumference (P>0.05).Conclusion: BASNEF model improved the infants' height and weight. Application of acupressure also improved the infants' height, weight, and head and arm circumference compared to the control group. Hence, learning and application of techniques and models by the medical team are highly essential.